LINGUISTIC MECHANISMS AND RHETORICAL TOOLS OF MANIPULATION IN POLITICAL TEXTS - Sarsenova Ulbosin Bazarbay kizi,Mamatkulova Saida Shukurjonovna (International Journal of Literature and Language Studies, 2026)
This article explores the linguistic mechanisms and rhetorical tools of manipulation within political discourse, with a specific focus on the challenges they present in translation. Drawing upon the critical discourse analysis frameworks of Charteris-Black, Van Dijk, and Fairclough, the study examines four primary manipulative instruments: conceptual metaphors, euphemisms and dysphemisms, lexical repetition, and syntactic structures. The analysis reveals that these tools function as